Analysis of Increasing Performance Effectiveness as an Effort to Sustain Village-Owned Enterprises in the Ngargoyoso Region, Karanganyar Regency - Dimas Ilham Nur Rois; Raisa Aribatul Hamidah; Dheny Hendrawan (International Journal of Economics, Business and Innovation Research, 2024)
Good corporate governance is the key to a company's long-term survival. Many BUMDes have died because they do not implement good corporate governance. The purpose of this study is to analyse the increase in performance effectiveness as an effort to sustain Village-Owned Enterprises in the Ngargoyoso Region, Karanganyar Regency. This type of research is qualitative with data collection techniques, namely interviews, observation and documentation. The analysis used is descriptive with the stages of data reduction, data presentation, and conclusions. Data validity techniques include credibility tests and dependability tests. The results of the study are that Good Corporate Governance has not been implemented optimally and has not experienced optimal improvement. This is indicated by the effectiveness of BUMDes in achieving goals that have not been optimal overall. Most BUMDes have not succeeded in providing village original income according to target, which is caused by several factors such as limited capital, tight business competition, and low public awareness of the role of BUMDes. The effectiveness of BUMDes in managing resources has mostly been running well, although there are some that have not been fully optimal in managing village assets, such as many assets that have not been utilized optimally. Most BUMDes have routinely conducted internal evaluations with the village government at the end of each month. This evaluation is important to assess BUMDes performance periodically and provide opportunities for operational improvement. The majority of the community has felt the benefits of programs run by BUMDes. The Berjo Village community, for example, received assistance distributed to each hamlet for the Independence Day celebration activities.